2022
DOI: 10.3390/cells11182776
|View full text |Cite
|
Sign up to set email alerts
|

Killer-Cell Immunoglobulin-like Receptor Diversity in an Admixed South American Population

Abstract: Natural Killer (NK) cells are innate immune cells that mediate antiviral and antitumor responses. NK cell activation and induction of effector functions are tightly regulated by the integration of activating and inhibitory receptors such as killer immunoglobulin-like receptors (KIR). KIR genes are characterized by a high degree of diversity due to presence or absence, gene copy number and allelic polymorphism. The aim of this study was to establish the distribution of KIR genes and genotypes, to infer the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 100 publications
1
3
0
Order By: Relevance
“…Consistent with the findings of previous studies, HLA-C was the most common ligand, along with HLA-Bw4, with an approximate frequency of 85%. The researchers also observed a low prevalence of KIR haplotype A, constituting only 13% of the population, aligning with findings in other Central and South American populations [ 55 ]. In another study involving a Brazilian cohort [ 45 ], researchers observed KIR frequencies exceeding 90% for KIR2DL1 , KIR2DL3 , KIR3DL1 (inhibitory KIR), KIR3DS1 (activating KIR), and KIR2PD1 (pseudogene).…”
Section: Hla/kir Interaction and Association With Diseasesupporting
confidence: 86%
See 1 more Smart Citation
“…Consistent with the findings of previous studies, HLA-C was the most common ligand, along with HLA-Bw4, with an approximate frequency of 85%. The researchers also observed a low prevalence of KIR haplotype A, constituting only 13% of the population, aligning with findings in other Central and South American populations [ 55 ]. In another study involving a Brazilian cohort [ 45 ], researchers observed KIR frequencies exceeding 90% for KIR2DL1 , KIR2DL3 , KIR3DL1 (inhibitory KIR), KIR3DS1 (activating KIR), and KIR2PD1 (pseudogene).…”
Section: Hla/kir Interaction and Association With Diseasesupporting
confidence: 86%
“…In a mixed Colombian population of European (75%), African (7%), and Native American (18%) descent, characterization of KIRs based on polymerase chain reaction sequence-specific oligonucleotide (PCR-SSO) revealed KIR2DP1 and KIR2DL1 to be most prevalent, accounting for 77% of the population [ 55 ]. Consistent with the findings of previous studies, HLA-C was the most common ligand, along with HLA-Bw4, with an approximate frequency of 85%.…”
Section: Hla/kir Interaction and Association With Diseasementioning
confidence: 99%
“…However, further validation of this observation in an independent cohort with various HCV-genotypes is recommended. The KIR diversity between different populations reported by other groups [13,14] is not a likely explanation as there was no statistically significant difference between the frequency of KIR allelotype in the non-cancer HCV patients in the Italian cohort and the Egyptian cohort (25.6% vs. 27%, p = 0.8843).…”
Section: Discussionmentioning
confidence: 77%
“…The discoveries about KIR polymorphism, KIR gene content, and copy number/KIR allelic variation have guided the research into the impact of KIR genetic variation on human health. [13][14][15] Due to its high level of diversity, the Brazilian population represents a unique group for research purposes. Thus, the main aim of this research was to investigate the presence of KIR genes in Brazil, and draw comparisons with other populations.…”
Section: Introductionmentioning
confidence: 99%